PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT TIGA SATU DINAMIKA JAKARTA SELATAN - Fiani, Nurrahma; Agrasadya (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to find out the influence of leadership and work discipline on employee performance at PT Tiga Satu Dinamika, South Jakarta, both partially and simultaneously. The method used in this research is a quantitative descriptive method. The sampling technique used was a saturated sampling technique with a sample of 52 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, descriptive analysis, simple regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that leadership has a significant effect on employee performance with the regression equation Y = 17.271 + 0.627 X1, a correlation coefficient of 0.709, meaning that the two variables have a strong relationship. The value of determination or contribution of influence is 0.502 or 50.2%, while the remaining 49.8% is influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (7.100 > 2.009). Thus, H0 is rejected and Ha is accepted, meaning that there is a significant influence between leadership on employee performance. Work discipline has a significant effect on employee performance with the regression equation Y = 7.137 + 0.811 The value of determination or contribution of influence is 0.737 or 73.7%, while the remaining 26.3% is influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (11.835 > 2.009). Thus, H0 is rejected and Ha is accepted, meaning that there is a significant influence between Work Discipline on employee performance. Leadership and Work Discipline have a significant effect on employee performance with the regression equation Y = 6.168 + 0.158 X1 + 0.688 X2. The correlation coefficient value or level of relationship between the independent variable and the dependent variable is 0.867, meaning it has a very strong relationship. The coefficient of determination or simultaneous influence contribution is 0.752 or 75.2%, while the remaining 24.8% is influenced by other factors. Hypothesis testing obtained a calculated F value > Ftable or (74.314 > 3,187). Thus H0 is rejected and Ha is accepted. This means that there is a significant simultaneous influence between leadership and work discipline on employee performance at PT Tiga Satu Dinamika, South Jakarta.